Long-Term Human Hematopoietic Stem Cell Culture in Microdroplets - Carreras, Pilar (Micromachines (Basel), 2021)
We previously reported a new approach for micromanipulation and encapsulation of human stem cells using a droplet-based microfluidic device. This approach demonstrated the possibility of encapsulating and culturing difficult-to-preserve primary human hematopoietic stem cells using an engineered double-layered bead composed by an inner layer of alginate and an outer layer of Puramatrix. We also demonstrated the maintenance and expansion of Multiple Myeloma cells in this construction. Here, the presented microfluidic technique is applied to construct a 3D biomimetic model to recapitulate the human hematopoietic stem cell niche using double-layered hydrogel beads cultured in 10% FBS culture medium. In this model, the long-term maintenance of the number of cells and expansion of hHSCS encapsulated in the proposed structures was observed. Additionally, a phenotypic characterization of the human hematopoietic stem cells generated in the presented biomimetic model was performed in order to assess their long-term stemness maintenance. Results indicate that the ex vivo cultured human CD34+ cells from bone marrow were viable, maintained, and expanded over a time span of eight weeks. This novel long-term stem cell culture methodology could represent a novel breakthrough to improve Hematopoietic Progenitor cell Transplant (HPT) as well as a novel tool for further study of the biochemical and biophysical factors influencing stem cell behavior. This technology opens a myriad of new applications as a universal stem cell niche model potentially able to expand other types of cells.